OGC P25 Outcomes of Laparoscopic Vs Open Oesophagectomy in a single high volume centre. (7th December 2022) - Hossain, Tanvir; Jackson, Andrew; Youssef, Fady; Trotter, Martin; Yanni, Fady; Zanotti, Daniela; Catton, James; Welch, Neil; Vohra, Ravi; Parsons, Simon L
Abstract: Background: Oesophageal cancer has a poor 5 year survival and surgery is the mainstay of curative treatment for the majority of cases. Minimally invasive surgery is practiced in a number of formats (open thorax/open abdomen, open thorax/lap abdomen, thoracoscopic/lap abdomen) and its benefits have been subject to a number of trials. Methods: We interrogated a prospectively recorded database of oesophagogastric cancer surgery from a large single centre to compare oesophagectomy cases performed with curative intent comparing laparoscopic abdomen plus open thorax versus a totally open operation. Transhiatal oesophagectomies were excluded. Baseline data was compared to establish whether groups were equally matched and outcomes of length of stay, any complication, anastomotic leak, number of lymph nodes yielded, 30 day mortality and 90 day mortality were subject to statistical analysis. Missing data was not imputed. Results: Sixty-nine hybrid oesophagectomies (laparoscopic abdomen, open thoracic phase) and 373 totally open procedures were performed between January 2017-May 2022. Both groups were equally matched in terms of age, performance status, ASA, tumour site, gender ratio and histology. LOS was 11.6 vs 13.5 (lap vs open / days), P=0.72. Complication rate was 33.3% v 37.3% (lap vs open) P= 0.53. Anastomotic leak rate was 10.1% vs 8.9% (lap vs open) P=0.73. Number of lymph nodes yielded was 25.8 ± 2.17 vs 24 ± 0.59 (lap vs open, mean ± s.e). Thirty day mortality was 2.9% vs 2.17% (lap vs open) P=0.66. Ninety day mortality was 7.25% vs 4.19% (lap vs open) P=0.27. Conclusions: This 5 year dataset of equally matched laparoscopic abdominal phase vs totally open oesophagectomy procedures shows no statistically significant difference in the outcomes that were measured. The laparoscopic approach would be expected to inflict a lesser stress response than open surgery. Oesophagectomy along with possible complications may inflict a stress response that masks the benefits from laparoscopic surgery. This data supports the notion that the laparoscopic abdomen approach is not inferior to an open procedure. Interrogation of a larger 10 year dataset would be worthwhile to confirm this. Furthermore, this current study may be merely be reflective of the learning curve for the laparoscopic approach and a prospective study of our practice will be worthwhile.